Steven D. Anderson – A.D. Riddle – Todd Bolen, Photo Companion to the Bible. The Gospels. I. Matthew. II. Mark. III. Luke. IV. John (www.BiblePlaces.com 2017) - Kubiś, Adam (Verbum vitae, 2018)
Recenzja:Steven D. Anderson – A.D. Riddle – Todd Bolen, Photo Companion to the Bible. The Gospels. I. Matthew. II. Mark. III. Luke. IV. John (www.BiblePlaces.com 2017). DVD & download. 299 USD